ADDRESSING THE MANAGEMENT OF AREAS AND SLUMS IN MOJOKERTO IN ACCORDANCE WITH THE SDG'S FRAMEWORK - Julkarnain, Donny Setyaelvanda; Bisri, Mohammad; Khusaini, Moh.; Wijaya, Andy Fefta (Transpublika Publisher, 2024)
This study aims to analyze the existing conditions of handling areas and slums in Mojokerto in accordance with the SDG's framework, and determine the dominant factors that influence the handling of areas and slums in the region. The research method used is Mix Method. The results of the analysis show that the existing condition of slum areas in Kedungmaling Village, Sooko Sub-district, Mojokerto District falls into the Moderate Slum category. However, there are no factors that can be included in the logistic equation model in multivariate analysis with logistic regression on the analysis parameters for safe and resilient cities/settlements. In the context of the SDG's framework, the handling of slum areas and settlements in Mojokerto needs to be evaluated by taking into account the dimensions of sustainable development compiled in the SDG's concept, as well as the indicators used to measure (Sustainable Cities and Communities) in the SDG's. Thus, a strategy for handling slum areas and settlements in Mojokerto can be developed. Thus, strategies for handling slum areas and settlements can be developed that are more in line with the principles of sustainable development included in the SDG's.